POLITIK TUTUP JALAN - La Ode Efrianto; Ramalan La Ode; Laode Harjudin; Dasmin; Lusianai Wa Ode (Halu Oleo University, 2024)
This paper describes the background of the resistance carried out by the people in three villages (Laiba, Laimpi and Wakumoro) as a form of unrest that they experienced as a result of the damage to the cross-provincial roads that had not been repaired for years by the Southeast Sulawesi provincial government. What is also interesting is that many resistance movements were pioneered by groups of mothers and resistance movements that were formed purely from the community groups themselves without depending on certain mass organizations. Using qualitative descriptive research methods. Data collection techniques through in-depth interviews and documentation studies. Interactive data analysis technique according to Milles Humerman and Saldana (2014). Community resistance against the government uses two methods of resistance, namely open reciprocity and closed resistance (James C. Scott, 2000). First, open resistance in the form of demonstrations, media hammering movements, and ina-ina resistance. Second, closed resistance is in the form of discussion of closed meetings, mass mobilization, strengthening the ideology of the movement and equalizing the vision of resistance. This research found that resistance that emerged organically then developed into a consistent resistance carried out by 3 villages (Laimpi, Laiba and Wakumoro Villages), so as to achieve the desired goals. Namely, the budgeted repair of the road.